Educação matemática e linguística nos jornais pedagógicos para professores das escolas de imigração alemã do sul do Brasil - Knijnik, Gelsa; Bredemeier, Maria Luísa Lenhard; Wanderer, Fernanda (Diálogos Latinoamericanos, 2017)
The paper discusses issues concerning the educational field linked to German immigration to Southern Brazil that began in 1824. Specifically, it aims at analysing discourses on mathematics and linguistic education in schools that circulated in two pedagogical journals addressing teachers at German immigrants’ schools of the southernmost state of Brazil, in the first third of the twentieth century. The first was published by the Catholic German-Brazilian Teachers’ Association and the second by the Evangelic German-Brazilian Teachers’ Association. Based on Foucaultian theorizations and late Wittgenstein ideas, the study shows that one of the statements presented in both discourses was related to the importance of using, in classroom, elements of non-school forms of life and that this statement interwove, in different ways, with statements that shaped the pedagogical discourse of that epoch.